2020
DOI: 10.3390/condmat5010004
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Quantum Kicked Rotor as A Continuous-Time Quantum Walk

Abstract: We analytically investigate the analogy between a standard continuous-time quantum walk in one dimension and the evolution of the quantum kicked rotor at quantum resonance conditions. We verify that the obtained probability distributions are equal for a suitable choice of the kick strength of the rotor. We further discuss how to engineer the evolution of the walk for dynamically preparing experimentally relevant states. These states are important for future applications of the atom-optics kicked rotor for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(111 reference statements)
1
12
0
Order By: Relevance
“…Benedetti et al [8] described CTQW on dynamical percolation graphs with the goal of analyzing the effect of noise produced by randomly adding or removing graph edges. Delvecchio et al [9] analytically investigated the analogy between the CTQW in one dimension and the evolution of the quantum kicked rotor at quantum resonance conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Benedetti et al [8] described CTQW on dynamical percolation graphs with the goal of analyzing the effect of noise produced by randomly adding or removing graph edges. Delvecchio et al [9] analytically investigated the analogy between the CTQW in one dimension and the evolution of the quantum kicked rotor at quantum resonance conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the quantum kicked rotor has recently found still another application, namely in the realization of quantum walks [30][31][32]. Our contribution [33] proves the analogy between a continuous-time quantum walk [34] with the kicked-rotor evolution at quantum resonance conditions [12], a research motivated by my joint work with Shmuel!…”
mentioning
confidence: 65%
“…This procedure is discussed in detail in Ref. [8]. Figures 1(b,c,d) show data for several momentum distributions obtained by the initial states of width three.…”
Section: Preparation Of the Basis For The Searchmentioning
confidence: 99%
“…In Ref. [8] some of us observed that the QKR at resonance conditions realizes a simple one-dimensional continuous-time quantum walk (CTQW). In the jargon of QWs, a CTQW is characterized by the absence of the degree arXiv:2002.09139v1 [quant-ph] 21 Feb 2020 of freedom given by the coin, as described, e.g., by [3,9].…”
Section: Introductionmentioning
confidence: 99%